The ethics of competition: accountability policy enactment in Chilean schools' everyday life - Falabella, Alejandra (Journal of education policy, 2020)
Public policies have a moral order, an ethical horizon. They offer a vocabulary of imagined micro-policies. Using the case of Chile, this paper examines the ways in which accountability policies are reworked within schools and how they affect actors' subjectivities. It adds new findings to the existing body of research on school accountability policies, offering in-depth evidence based on the case of Chile, which has a high-stakes testing model and a widespread competitive voucher system. The research is based on case studies of ten public and private subsidised schools, framed by a sociological perspective of policy enactment theory. The research findings show the ways that accountability policies are recreated, expanded, and intensified at the local level, permeating an ethic of competition. The analysis focuses on three qualitative trends: school actors' sense-making of test scores and labels; zones of safety and risk for teachers under an accountability regime; and the emergence of a sticky web of persuasion, surveillance, and coercion among school members in order to improve performance. The practices examined are not understood as 'secondary effects' or an 'implementation problem', as if they occur unconnected from the policy rationale. The outcomes are consistent with the policy itself in interaction with school life.